REVISITING ONE-STEP AND TWO-STEP FLOW THEORIES IN MASS COMMUNICATION: A COMPARATIVE ANALYSIS IN THE DIGITAL ERA - Muhammad Afrezal Nasution; Azriel Ivan Akbar; Muhammad Amri Daulay; Muhammad Zulfahmi Azmi Dalimuthe (Academic Solution Publisher, 2026)
This study revisits the one-step flow and two-step flow theories to examine their relevance in contemporary mass communication within the digital era. Using an integrative literature review with a comparative-analytical approach, the study analyzed 28 selected sources, consisting of foundational and contemporary publications on media effects, opinion leadership, digital communication, and platform-based interaction. The findings show that the one-step flow model remains useful for explaining rapid, direct, and large-scale message dissemination, particularly in situations requiring consistency and immediacy. However, it is limited in explaining how audiences interpret, negotiate, and respond to messages within complex social environments. By contrast, the two-step flow model offers a more flexible explanation of mediated influence, especially where credibility, interpersonal communication, and social legitimacy shape message acceptance. In digital contexts, both models remain relevant but need to be reconsidered alongside multi-step flow, networked influence, algorithmic curation, and hybrid media ecologies in contemporary Indonesian communication research and practice.